ChemInform Abstract: High‐Pressure Investigations of Lanthanoid Oxoarsenates. Part 1. Single Crystals of Scheelite‐Type Ln[AsO4] Phases with Ln: La—Nd from Monazite‐Type Precursors. Issue 32 (22nd July 2016) - Metzger, Sebastian J.; Ledderboge, Florian; Heymann, Gunter; Huppertz, Hubert; Schleid, Thomas
Abstract: Transparent single crystals of Ln[AsO4 ] (Ln: La—Nd) are obtained by the pressure‐induced monazite‐to‐scheelite type phase transition (Walker‐type multi‐anvil cell, 11 GPa, 1100—1300 °C, 15 min).